Cross-Cultural Adaptation and Psychometric Validation of the Medication Compliance Questionnaire (MCQ) for Type 2 Diabetes Mellitus Patients in Indonesia - Wibowo, Much Ilham Novalisa Aji; Safitri, Angelia Yuliana; Setiawan, Didik (UI Scholars Hub, 2025)
Background: Medication adherence is critical for managing type 2 diabetes mellitus (T2DM). The Medication Compliance Questionnaire (MCQ) is a widely recognized tool for assessing adherence but has not been adapted for T2DM in Indonesia. This study aimed to adapt and validate the MCQ in the Indonesian socio-cultural context. Methods: A cross-sectional study at community health centers (May–Aug 2024) involved forward/back translation, content validation using Aiken’s V, and psychometric assessment among 230 patients. Exploratory Factor Analysis (EFA) assessed construct validity, including convergent, discriminant, and reliability. Results: Aiken's V index indicated strong content validity (average = 0.881). EFA identified two dimensions—practical adherence and patient perception—explaining 49.25% of the variance. Composite Reliability (CR) values exceeded 0.70, indicating good internal consistency. While the Average Variance Extracted (AVE) was below 0.50, CR ≥ 0.70 confirmed convergent validity. No significant cross-loadings supported discriminant validity. Conclusion: The validated Indonesian version of the MCQ consists of six items, demonstrating strong validity and reliability. The two-factor structure reflects practical adherence and patient perception, making it a valuable tool for assessing medication adherence among Type 2 Diabetes Mellitus (T2DM) patients in Indonesia.